Odpowiedzi

2009-09-23T16:29:40+02:00
A) A= (2,3) i B = (4,5 )
y=ax+b
{ 3=2a + b
{ 5=4a +b

{-2a-b=-3 / * (-1)
{4a-b=-5

{2a+b=3
{4a-b=-5
_______________
6a=2//:6
a=2/6

a=2/6
2*2/6+b=3
b-3-2/3=2
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-09-23T16:35:33+02:00
A) A= (2,3) i B = (4,5 )
y=ax+b
3=2a+b
5=4a+b
-b=2a-3
b=-2a+3
5=4a-2a+3
5=2a+3
-2a=3-5
-2a=-2
a=1
b=-2+3
b=1
y=x+1

b) A= (-2,3) i B = ( 4, -5 )
y=ax+b
3=-2a+b
-5=4a+b
-b=-2a-3
b=2a+3
-5=4a+2a+3
-5=6a+3
-6a=3+5
-6a=8
a=-8/6
a=-4/3
b=2*(-4/3)+3
b=-8/3+3
b=1/3
y=-4/3x+1/3

c) A = ( 2,0 ) i B = ( -2,6)
0=2a+b
6=-2a+b
-b=2a
b=-2a
6=-2a-2a
4a=-6
a=-6/4
a=-3/2
b=-2*-3/2
b=6/2
b=3
y=-3/2x+3

d) A= (-2,0) i B= (0,6 )
0=-2a+b
6=b
0=-2a+6
2a=6
a=3
y=3x+6






2009-09-23T17:02:37+02:00
A) A= (2,3) i B = (4,5 )

y=ax+b
x=2, y=3
x=4, y=5
korzystasz ze wzoru:

{ 3 = 2a + b
{ 5 = 4a + b

{-2a-b=-3 / * (-1)
{ 4a-b=-5

{2a+b=3
{4a-b=-5

6a=2/:6
a=2/6
a=1/3

2a+b=3 podstawiasz za a=1/3

2*1/3+b=3
2/3+b=3
b=3-2/3
b=9/3-2/3
b=7/3
b=2 1/3